APLIKASI BIOCHAR DAN PUPUK N TERHADAP SIFAT KIMIA TANAH LAHAN KERING DAN PERTUMBUHAN SORGUM - Jelita, Fransiska Delafira; Hamzah, Amir; Hapsari, Ricky Indri; Wilujeng, Retno (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
This study aims to determine how the application of rice husk biochar and nitrogen fertilizer (urea), affects the chemical properties of dryland soil and the vegetative growth of sorghum (Sorghum bicolor L. Moench). This study was conducted from September 2024 to March 2025 at the Science Techno Park of Tribhuwana Tunggadewi University in Malang, East Java, using a Factorial Randomized Block Design with two factors: urea doses (0, 100, 150 and 200 kg ha-1) and biochar (0 and 5 tons ha-1) three replications. The parameters observed were pH H2O, total N-P-K, Organic-C, plant height, stem circumference, number of leaves, and leaf length and width. The results showed that the use of rice husk biochar and N fertilizer in dryland significantly interacted only on the parameter of sorghum plant height at 8 WAP. The use of the N3 dose (urea fertilizer dose of 200 kg ha-1) showed the most optimal results, but the N2 treatment (urea fertilizer dose of 150 kg ha-1) can be considered more efficient because the use of a lower dose of N fertilizer (urea) produced results that were not significantly different from the N3 treatment. Treatment B1 (5 t biochar ha-1) showed better results than B0 (no treatment).